Предмет: Математика, автор: andreykabobrov00

Помогите решить задание. Дам 30 баллов.

Приложения:

Ответы

Автор ответа: NNNLLL54
1

f(x)=\frac{x^2-4}{x^2+4}\\\\f'(x)=\frac{2x\, (x^2+4)-2x\, (x^2-4)}{(x^2+4)^2}=\frac{16x}{(x^2+4)^2}\\\\f'(-1)=\frac{-16}{5^2}=-\frac{16}{25}=-0,64

Автор ответа: table123
1

Ответ: -16/25

Пошаговое объяснение:

f(x)=x^2-4/ x^2+4,  формула   (u/v)'=(u'v-uv')/v^2,  

f"(x)=(2x*(x^2+4)-(x^2-4)*2x)/(x^2+4)^2=(2x^3+8x-2x^3+8x)/(x^2+4)^2=16x/(x^2+4)^2,   f'(-1)=16*(-1)/(1+4)^2=-16/5^2=-16/25

Похожие вопросы